Assessment of mobile phone usage and self-perceived effects among students of a dental college in Chennai. - BARMA, MANALI DEB; D, SRISAKTHI; INDIRAN, MEIGNANA ARUMUGHAM; KUMAR R, PRADEEP (The journal of contemporary issues in business and government, 2020)
Mobile phone addiction is a type of technological addiction or non substance addiction. The present study was conducted with the objectives of assessing an existing Mobile Phone Dependence Questionnaire scale among dental students and to assess the pattern and factors associated with mobile phone addiction-like behaviour. Nomophobia literally means no mobile phobia that is the fear of being out of mobile phone contact. A cross-sectional study with 177 participants was conducted with Mobile Phone Dependence Questionnaire self administered questionnaire among students of a dental college in Chennai. The questionnaire had demographic details and questions assessing their mobile phone pattern use and self perceived effects of mobile usage on health. Data was collected using a questionnaire. Descriptive statistics were used to analyze the data. Among the study participants, 64% were above the age of 20. Around 59.3% used their phones for more than 4 hours, however no statistically significant association was observed between gender and duration of phone usage (p <0.05). About 45.8% reported they used their phones during class hours too. Eye strain was the most perceived effect among the participants. The present study results showed that the usage of mobile phones among the study participants was high, which is consistent with the rising trend of usage of mobile phones. . Mass media efforts should be made to raise awareness among people regarding the health effects of mobile phones and regulatory guidelines to reduce its exposure and using mobiles judiciously to avoid becoming independent of technology.